Preparation and application of palladium cluster catalyst capable of accurately positioning edges of nanosheets
By accurately positioning the palladium clusters at the edges of carbon-nitrogen polymer nanosheets, an efficient catalyst was prepared, which solved the problems of low catalytic activity and insufficient stability of traditional catalysts, achieved efficient and sustainable catalytic effects, and provided prospects for industrial applications. .
Patent Information
- Application Number
- CN202411584655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
The traditional catalytic dehydrogenation preparation of dipentene has problems such as insufficient catalytic activity, poor stability and high cost on the catalysts of umbilical hydrocarbons, which limits its wide application in industrial production.
By accurately positioning the palladium cluster at the edge of carbon and nitrogen polymer nanosheets, a palladium cluster catalyst was prepared to accurately position the palladium cluster catalyst at the edge of the nanosheet, which significantly reduced the amount of palladium and prevented the agglomeration of palladium while maintaining high catalytic efficiency. shedding and loss from the carrier.
The catalyst has high catalytic activity, excellent stability and good recycling performance, which significantly extends the recycling life of the catalyst, reduces palladium consumption, improves the selectivity and stability of the catalyst, and provides a broad range of industrial applications. prospect.
Smart Images

Figure CN119456006A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a nanosheet edge precisely positioned palladium cluster catalyst, belonging to the technical field of catalyst preparation and biomass conversion. Background Art
[0002] As global energy shortages intensify and fossil energy prices continue to rise, the development and utilization of renewable resources has become one of the key strategies to promote sustainable energy development. Dipentene has become a renewable resource with great potential due to its wide sources and low cost. Dipentene is a by-product of turpentine in industrial processes such as the synthesis of terpineol and camphor, and is also one of the important components of waste tire pyrolysis oil. In the chemical industry, dipentene can be used to prepare para-cymene through catalytic dehydrogenation. As an important intermediate in fine chemicals, para-cymene is widely used in pesticides, medicines, synthetic materials and other fields, and has huge market demand. The process of preparing para-cymene through catalytic dehydrogenation of dipentene can not only reduce dependence on fossil resources, but also effectively improve the high-value utilization rate of renewable resources and promote the sustainable development of green chemicals.
[0003] At present, the catalysts commonly used in the process of preparing p-cymene by catalytic dehydrogenation of dipentene mainly include palladium-based precious metal catalysts (such as palladium carbon) and nickel-based catalysts (such as Raney nickel) (Applied Catalysis A, 1999, 188 (1-2): 287; Applied Catalysis A, 1997, 158 (1-2): 145; Chemistry and Industry of Forest Products, 1993, 13 (4): 305). Although the palladium carbon catalyst has a high yield (> 80%) in the catalytic dehydrogenation reaction of dipentene, its stability is poor, and the agglomeration and shedding of palladium nanoparticles are prone to occur, resulting in a reduction in active sites. In addition, the palladium carbon catalyst is difficult to effectively recover after the reaction, and the recovery process is complicated and easily causes the loss of palladium, further increasing the production cost. In contrast, although Raney nickel is cheap, its catalytic activity and selectivity are far inferior to those of palladium carbon catalysts. The yield of p-cymene is only about 60-70%, and it is sensitive to reaction conditions, easily deactivated, and has poor stability for recycling. Therefore, traditional catalysts generally have problems such as insufficient catalytic activity, poor stability and high cost, which limits their widespread application in industrial production.
[0004] In response to these problems, the present invention proposes a palladium cluster catalyst based on the precise positioning of the edge of a cyano-modified carbon-nitrogen polymer nanosheet. By precisely positioning the palladium cluster at the edge of the carbon-nitrogen polymer nanosheet, the amount of palladium used is significantly reduced, and while maintaining a high catalytic efficiency, the aggregation of palladium and its shedding and loss from the carrier are prevented. This technology increases the active specific surface area of the catalyst, ensures the provision of sufficient active sites, significantly extends the cycle life of the catalyst, reduces palladium consumption, and improves the catalyst selectivity and stability in the process of dehydrogenating dipentene to prepare para-cymene, providing broad prospects for its industrial application. Summary of the invention
[0005] The present invention provides a preparation method and application of a nanosheet edge precision positioning palladium cluster catalyst. The prepared nanosheet edge precision positioning palladium cluster catalyst has high catalytic activity, is suitable for the catalytic dehydrogenation reaction of dipentene, and can effectively prepare p-cymene. The catalyst not only has high stability, but is also easy to recycle and reuse; and significantly reduces the amount of palladium used, while also reducing the amount of catalyst used, reducing the catalytic reaction temperature, and shortening the reaction time.
[0006] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0007] A method for preparing a palladium cluster with precise positioning on the edge of a nanosheet, comprising the steps of subjecting a nitrogen-containing precursor to a first calcination to obtain a carbon-nitrogen polymer solid powder, followed by a second calcination, and forming a cyano-modified carbon-nitrogen polymer nanosheet with a highly active edge site through a thermal stripping process, wherein the palladium is precisely positioned through the strong coordination between the cyano group and the edge active site, and the palladium cluster is further better dispersed on the edge of the nanosheet by adding a stabilizer in combination with a chemical reduction method, thereby obtaining a palladium cluster with precise positioning on the edge of the nanosheet; the loading amount of palladium relative to the cyano-modified carbon-nitrogen polymer nanosheet carrier is 0.5-1.5wt%; and the stabilizer is at least one of polyvinyl pyrrolidone, polyethylene glycol, polyethyleneimine, polyvinyl alcohol or sodium carboxymethyl cellulose.
[0008] The above catalysts exhibit high catalytic performance, excellent stability and good recycling performance.
[0009] The invention significantly reduces the amount of palladium used, and also reduces the amount of catalyst used, reduces the catalytic reaction temperature, and shortens the reaction time.
[0010] In the present invention, the alkali metal halide salt is omitted in the secondary roasting.
[0011] The first step of calcination converts precursors such as melamine or urea into common carbon-nitrogen polymers through thermal polymerization. This step mainly generates basic materials, providing structural support for subsequent surface modification and catalytic applications.
[0012] The second step of calcination is to treat the carbon-nitrogen polymer through a thermal exfoliation process to destroy its layered structure and form a nanoscale thin layer structure, namely a nanosheet. During this process, some carbon or nitrogen atoms escape, resulting in carbon / nitrogen vacancies and unsaturated active sites, which reduce the crystallinity of the material. At the same time, the introduction of cyano functional groups on the surface enhances the reactivity and adsorption capacity of the material, providing ideal conditions for the precise positioning and uniform loading of palladium clusters.
[0013] Carbon-nitrogen polymer is a two-dimensional layered covalent compound composed of carbon and nitrogen elements. The basic unit is a polymer of heptazine rings or triazine rings, which has high thermal and chemical stability. As a catalyst carrier, carbon-nitrogen polymer nanosheets can effectively disperse metal nanoclusters, prevent agglomeration, and improve catalytic activity and stability due to their large specific surface area and abundant active sites. The π-conjugated system of carbon-nitrogen polymer can also enhance electron transfer, reduce reaction activation energy, and accelerate reaction rate.
[0014] Precise positioning is achieved by controlling the distribution of palladium clusters on the surface or edge of carbon-nitrogen polymers so that they are evenly distributed on specific active sites, thereby improving catalytic activity and stability. Palladium clusters are composed of 2 to dozens of palladium atoms, and can be observed to be distributed at the edge of carbon-nitrogen polymer nanosheets by spherical aberration-corrected transmission electron microscopy. The presence of cyano groups induces palladium clusters to selectively adsorb on the edge sites of nanosheets through their coordination ability, edge-preferred modification effect, and electronic structure regulation. Due to the high reactivity and unique electronic structure of the edge, cyano groups are more likely to modify these areas and firmly fix the palladium clusters on low-energy adsorption sites through strong coordination, thereby achieving precise positioning. In addition, stabilizers significantly improve the dispersibility and stability of palladium clusters through multiple mechanisms such as preventing agglomeration, enhancing binding force, and balancing electron distribution. The steric hindrance effect of stabilizers forms a physical barrier between palladium clusters, effectively preventing agglomeration and maintaining a highly dispersed state at the nanoscale. The functional groups of the stabilizers form weak coordination bonds with palladium atoms, enhancing the adhesion of palladium clusters to the carrier and avoiding shedding during the reaction. Stabilizers can also balance the electronic distribution of palladium clusters and optimize the electronic environment of active sites. Through these synergistic effects, palladium clusters can be more evenly and precisely distributed at the edges of nanosheets, greatly improving the stability and reusability of the catalyst.
[0015] The mass ratio of the cyano-modified carbon-nitrogen polymer nanosheet to the stabilizer is 1:(0.5-10), and the concentration of the stabilizer is 1-10 g / L.
[0016] The above stabilizer is preferably polyvinyl pyrrolidone.
[0017] The chemical reduction method is used to load metal palladium on the cyano-modified carbon nitrogen polymer nanosheets. The specific steps include: uniformly mixing the cyano-modified carbon nitrogen polymer nanosheet catalyst powder, water and stabilizer, then adding palladium chloride-hydrochloric acid solution, heating under oil bath conditions for reaction; then adjusting the pH to alkaline, adding sodium borohydride solution for reduction, and then centrifugation, water washing, ethanol washing, vacuum drying and grinding in sequence to obtain a cyano-modified carbon nitrogen polymer nanosheet edge precise positioning palladium cluster catalyst. The oil bath heating reaction conditions are 50-95°C, the oil bath reaction time is 0.5-10 hours, and the pH is adjusted to 9-12.
[0018] The mass volume ratio of the cyano-modified carbon nitrogen polymer nanosheets to the palladium chloride-hydrochloric acid solution is 1:(3-10); the mass ratio of the cyano-modified carbon nitrogen polymer nanosheets to sodium borohydride is 1:(0.01-0.1); the concentration of palladium chloride in the hydrochloric acid-palladium chloride solution is 0.5-200mmol / L, the concentration of hydrochloric acid is 0.1-3mol / L, and the concentration of the sodium borohydride solution is 0.05-0.5mol / L.
[0019] In the first calcination process, the nitrogen-containing precursor is calcined in a muffle furnace or a tube furnace with a heating rate of 2-4°C / min and a holding temperature of 470-600°C, and is maintained at this temperature for 3-5 hours in an atmosphere of atmospheric pressure air or inert gas (such as nitrogen, argon), and then naturally cooled to room temperature and ground into a carbon-nitrogen polymer powder.
[0020] The nitrogen-containing precursor includes at least one of melamine, cyanamide, dicyandiamide, urea, cyanuric acid, thiourea, ammonium thiocyanate, guanidine thiocyanate, guanidine hydrochloride, semicarbazide, aminoguanidine, 2,4,6-triamino-1,3,5-triazine or 5-aminotetrazole.
[0021] The carbon-nitrogen polymer solid powder obtained by the first calcination is placed in a muffle furnace or a tubular furnace for a second calcination, with a heating rate of 0.5-1.5°C / min, heated to 200-300°C, and maintained at this temperature for 1-3 hours. The atmosphere in the muffle furnace is atmospheric pressure air or an inert gas (such as nitrogen, argon), and then naturally cooled to room temperature and ground into a cyano-modified carbon-nitrogen polymer nanosheet solid powder.
[0022] The nanosheet edge-precisely positioned palladium clusters prepared by the above preparation method are used as catalysts for the catalytic dehydrogenation of dipentene to prepare p-cymene;
[0023] The method for preparing p-cymene by catalytic dehydrogenation of dipentene comprises: stirring and mixing a catalyst and dipentene, placing the mixture in a reactor for reaction, filtering and separating the catalyst after the reaction, and analyzing the obtained liquid product by gas chromatography-mass spectrometry; centrifuging the catalyst, washing the precipitate, drying and grinding the precipitate, and then reusing the precipitate.
[0024] The mass ratio of the palladium cluster catalyst to dipentene is precisely positioned at (0.005-0.01):1, the reaction temperature is 150-210°C, the reaction time is 0.5-2 hours, the reaction pressure is 0.05-3MPa, the reaction atmosphere is argon or nitrogen, and the stirring speed is 100-1000rpm / min.
[0025] The specific method is: the catalyst and dipentene are mixed in a mass ratio of (0.005-0.01):1, placed in a reactor, stirred at a speed of 100-1000rpm / min, reacted at a temperature of 150-250°C for 0.5-10 hours, the reaction atmosphere is argon or nitrogen (0.05-3MPa), after the reaction is completed, the catalyst is separated and removed by filtration to obtain a liquid product, which is analyzed by gas chromatography-mass spectrometry. The catalyst can be reused after centrifugation, water washing, drying, and grinding.
[0026] The nanosheet edge-precisely positioned palladium cluster catalyst prepared by the present invention has efficient catalytic performance and good stability, and exhibits excellent effects in the catalytic dehydrogenation of dipentene to prepare para-cymene. It is easy to separate and recycle, and is suitable for industrial production applications. The present invention solves the problems of low catalytic activity and insufficient stability of traditional catalysts in the dipentene dehydrogenation reaction through the precise positioning of palladium nanoclusters and the unique carbon-nitrogen polymer nanosheet carrier structure, and provides an efficient and sustainable catalytic solution.
[0027] The present invention regards ≥99.999% as 100%.
[0028] The technologies not mentioned in the present invention are all referred to the prior art.
[0029] The beneficial effects of the present invention are:
[0030] (1) The present invention provides a method for preparing a cyano-modified carbon nitrogen polymer nanosheet edge-precision positioned palladium cluster catalyst, which maintains the small size and high activity of the palladium cluster and improves the overall catalytic performance in the catalytic dehydrogenation of dipentene to prepare para-cymene. The 1% Pd / V-CN of the present invention has a conversion rate of up to 100% and a selectivity of up to 100% in the dipentene dehydrogenation reaction, which is significantly better than traditional catalysts and has a broad-spectrum catalytic effect and high selectivity for a variety of hydrocarbons.
[0031] (2) The cyano-modified carbon-nitrogen polymer nanosheet edge-precisely positioned palladium cluster catalyst prepared by the present invention exhibits excellent stability in multiple cycles and can continuously maintain efficient catalytic performance. Through precise palladium cluster positioning technology, the rate of catalyst performance degradation is reduced, the frequency of catalyst replacement is reduced, and the service life is extended, thereby improving the economy and convenience of operation.
[0032] (3) The preparation method of the present invention effectively reduces the amount of palladium used, thereby reducing the cost of using the precious metal palladium. This method not only improves the economic benefits of the catalyst, but also makes the precisely positioned palladium cluster catalyst have a higher cost-effectiveness in large-scale industrial applications, thereby improving its economic feasibility in industrial production. Compared with the traditional 10% palladium carbon catalyst, the 1% Pd / V-CN catalyst of the present invention has a palladium loading reduced by 90%, and the amount of palladium used is greatly reduced, thereby significantly reducing the cost of using the catalyst and ensuring a balance between effect and cost.
[0033] (4) The present invention achieves efficient catalysis under milder reaction conditions through lower palladium loading and precise positioning of palladium cluster technology, thereby reducing energy consumption and cost, significantly reducing the amount of palladium used, and also reducing the amount of catalyst used, lowering the catalytic reaction temperature, and shortening the reaction time. The catalytic reaction can be completed at 200°C in 2 hours, with significantly improved efficiency, significantly reduced energy consumption, lower equipment cost and energy consumption requirements, and greater economy.
[0034] (5) The present invention shows significant advantages in terms of recyclability and p-cymene content, and has better cycle stability and economy. The mass recovery rate of the catalyst is maintained at more than 95%. After 15 cycle experiments, the dipentene conversion rate of the 1% Pd / V-CN catalyst is still maintained at 98%, and the p-cymene selectivity is also maintained at 97%. The relative content of p-cymene in the product is 96%, which is suitable for large-scale industrial applications and has higher economy and competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The scanning electron microscope images of (a) 1% Pd / V-CN prepared in Example 1 of the present invention and (b) 1% Pd / CN prepared in Comparative Example 1;
[0036] Figure 2 This is a spherical aberration corrected transmission electron microscope image of 1% Pd / V-CN prepared in Example 1 of the present invention;
[0037] Figure 3 This is a spherical aberration corrected transmission electron microscope image of 1% Pd / CN prepared in Comparative Example 1 of the present invention;
[0038] Figure 4 The nitrogen adsorption-desorption curves and pore size distribution diagrams of 1% Pd / V-CN prepared in Example 1 of the present invention and 1% Pd / CN prepared in Comparative Example 1;
[0039] Figure 5 X-ray powder diffraction patterns of the catalysts prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention;
[0040] Figure 6The infrared spectra of the catalysts prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention are shown;
[0041] Figure 7 The total ion current chromatograms of the gas chromatography-mass spectrometry reports of the dipentene dehydrogenation products of (a) 1% Pd / V-CN prepared in Example 1 of the present invention and (b) 1% Pd / CN prepared in Comparative Example 1; DETAILED DESCRIPTION
[0042] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0043] In the embodiment, the microscopic morphology of the sample is obtained by observing with a Verios G4 UC2 scanning electron microscope of the United States; the microscopic morphology and element distribution of the sample are obtained with the help of a Themis Z-type spherical aberration corrected electron microscope of the United States; the composition and crystal structure information of the catalyst are obtained by using a Japanese RigakuSmartlab X2 X-ray powder diffractometer; the chemical composition and functional group structure information of the catalyst are obtained by using a Nicoletis50 infrared spectrometer of the United States; the nitrogen adsorption-desorption curve information of the catalyst is detected by using a MicromeriticsASAP2460 physical adsorption instrument of the United States; the hydrogen temperature-programmed reduction and carbon dioxide temperature-programmed desorption information of the catalyst are detected by using a MicromeriticsAutoChem II 2920 chemical adsorption instrument of the United States; and the content of dipentene series components and para-cymene in industrial dipentene is obtained by using an Agilent Intuvo 9000-7000D2 triple tandem quadrupole gas chromatograph-mass spectrometer of the United States.
[0044] The conversion rate of dipentene and the selectivity of the dehydrogenated product to cymene were calculated according to formula (1) and formula (2), respectively.
[0045] Conversion rate of dipentene / % = (M D1 -M D2 ) / M D1 ×100(1)
[0046] Selectivity for cymene / % = M O / (M D1 -M D2 )×100(2)
[0047] Where M D1 Indicates the relative mass fraction of dipentene in the raw material; M D2 Represents the relative mass fraction of dipentene in the reaction product; M O It represents the relative mass fraction of p-cymene in the reaction product.
[0048] Example 1
[0049] a) Preparation of bulk carbon nitride polymer (CN): Weigh 5.0 g of melamine, place it in a muffle furnace and calcine it. Raise the temperature to 500°C at 2°C / min, calcine it for 4 hours, and naturally cool it to room temperature. The atmosphere is normal pressure air. Grind it to obtain a yellow powder, i.e., bulk carbon nitride polymer (CN).
[0050] b) Preparation of carbon nitrogen polymer nanosheets (V-CN): Weigh 0.5 g CN, place it in a muffle furnace and calcine it. Raise the temperature to 250° C. at 1° C. / min, calcine it for 2 hours, cool it naturally to room temperature, and grind it to obtain a white powder to obtain cyano-modified carbon nitrogen polymer nanosheets (V-CN).
[0051] c) Preparation of palladium-supported cyano-modified carbon nitrogen polymer (Pd / V-CN): Add 0.2g V-CN to a 100mL round-bottom flask, then add 50mL of 6.3g / L polyvinyl pyrrolidone (Shanghai Aladdin Biochemical Technology Co., Ltd., average molecular weight 58000, K29-32, AR) aqueous solution, mix well, and heat in an 80℃ oil bath for 10 minutes. Weigh 3.3mg palladium chloride in a 5mL centrifuge tube, add 2mL of 2mol / L hydrochloric acid to dissolve, add to the flask, and react at 80℃ for 12 hours. After cooling to room temperature, add 1mol / L sodium hydroxide solution to adjust the pH to 10, slowly (30 drops / min) add 1.1mL 0.1mol / L sodium borohydride solution (sodium borohydride mass is about 4mg), react at room temperature for 2 hours, and filter and separate. The precipitate was washed with water until neutral, then with ethanol, dried under vacuum at 60°C for 12 hours, and ground with an agate mortar to obtain a solid powder (with a particle size of less than 100 microns) to obtain a 1% Pd / V-CN catalyst.
[0052] d) Catalytic dipentene dehydrogenation performance test: Under 0.1 MPa argon protection, 0.05 g of 1% Pd / V-CN catalyst and 5 g of industrial dipentene (Fujian Nanping Qingsong Chemical Co., Ltd.) were stirred and mixed, placed in a reactor, stirred at 300 rpm / min, and reacted at 200° C. for 2 hours. After the reaction, the solid catalyst was separated by filtration, the liquid product was collected and diluted with methanol, placed in a sample bottle, and the contents of the reactant dipentene and p-cymene product were analyzed by gas chromatography-mass spectrometry, the peak area was normalized, the conversion rate of dipentene and the selectivity of p-cymene were calculated, and the catalytic dipentene dehydrogenation effect was evaluated.
[0053] The industrial dipentene raw materials used in each example have a total mass fraction of 89.38% of four components belonging to the dipentene series: α-terpinene, limonene, γ-terpinene and isoprene. It also contains 9.72% of p-cymene. Other impurities include a small amount of carene and camphene.
[0054] Example 2
[0055] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, but the amount of PdCl2 added was adjusted to 1.7 mg to accommodate 0.5% Pd loading, thereby obtaining a 0.5% Pd / V-CN catalyst.
[0056] Example 3
[0057] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, but the amount of PdCl2 added was adjusted to 10.0 mg to accommodate 3% Pd loading, thereby obtaining a 3% Pd / V-CN catalyst.
[0058] Example 4
[0059] The catalyst synthesis steps and the catalytic dehydrogenation performance test of dipentene were the same as those in Example 1, but the addition amount of PdCl2 was adjusted to 20.0 mg to adapt to 6% Pd loading, thereby obtaining a 6% Pd / V-CN catalyst.
[0060] Example 5
[0061] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that industrial dipentene was replaced by terpinene.
[0062] Example 6
[0063] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that industrial dipentene was replaced by γ-terpinene.
[0064] Example 7
[0065] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that industrial dipentene was replaced by limonene.
[0066] Comparative Example 1
[0067] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that 0.2 g of V-CN in step c) of Example 1 was replaced by 0.2 g of CN to obtain a 1% Pd / CN catalyst.
[0068] Comparative Example 2
[0069] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that in step d) of Example 1, only CN synthesized in step a) was used as a catalyst, and no Pd was loaded.
[0070] Comparative Example 3
[0071] The catalyst synthesis steps and the dipentene catalytic dehydrogenation performance test were the same as those in Example 1, except that in step d) of Example 1, only the V-CN synthesized in step b) was used as a catalyst, and no Pd was loaded.
[0072] Comparative Example 4
[0073] The catalytic dehydrogenation performance test of dipentene was the same as that of Example 1, except that commercial 10% palladium carbon (10% Pd / C, Shanghai BiDe Pharmaceutical Technology Co., Ltd.) was used as a catalyst in step d) of Example 1 instead of 1% Pd / V-CN.
[0074] Comparative Example 5
[0075] The catalytic dehydrogenation performance test of dipentene was the same as that of Example 1, but in step d) of Example 1, commercial Raney nickel (20-40 mesh, dispersed in water, Shanghai Roen Chemical Technology Co., Ltd.) was used as a catalyst instead of 1% Pd / V-CN.
[0076] Comparative Example 6
[0077] The catalytic dehydrogenation performance test of dipentene was the same as that of Example 1, except that in step d) of Example 1, hydrogen-type HZSM-5 molecular sieve (500 mesh, Si / Al=30, effective substance content>95%, Zibo Runxin Chemical Technology Co., Ltd.) was used as a catalyst instead of 1% Pd / V-CN.
[0078] Comparative Example 7
[0079] Preparation of highly crystalline carbon nitride (PHI): 8 g of melamine was weighed and heated at 5 °C min -1 The sample was heated to 500°C in a muffle furnace at a heating rate of 100 °C and then kept at a constant temperature for 4 h. The sample was cooled to room temperature naturally and ground into powder for later use. 600 mg of the ground powder sample was weighed and mixed with 3.3 g of potassium chloride and 2.7 g of lithium chloride. The sample was placed in a tube furnace under a nitrogen atmosphere at 5 °C·min -1 The sample was heated to 550℃ at a rate of 1000℃ and kept at this temperature for 4 hours, cooled to room temperature naturally, and ground into powder. Water was added for ultrasonic dispersion, and the sample was filtered three times to remove potassium chloride and lithium chloride from the sample. The sample was vacuum dried at 60℃, and then the sample was collected and ground into powder, which was named PHI.
[0080] Preparation of palladium-supported high-crystalline carbon nitride (Pd / PHI) catalyst: 25 mg of PdCl2, 2 mL of 2 mol / L hydrochloric acid (HCl mass concentration of 0.73 wt%) and 40 mL of water were added to a flask, 0.5 g of PHI powder was weighed, and after ultrasonic-assisted dispersion for 30 min, refluxed in an oil bath at 80°C, and immersed for 12 h under magnetic stirring. Then, NaOH solution was added to adjust the pH to 10, and 8 mL of 0.18 mol / L NaBH4 solution was slowly added (12 drops / min). After the addition was completed, the reaction was continued to be stirred in an oil bath at 80°C for 2 h, and centrifuged. The resulting precipitate was washed with water and ethanol in turn, and then dried in vacuum at 60°C to obtain 3% Pd / PHI, wherein the theoretical loading of Pd was 3 wt%.
[0081] Comparative Example 8
[0082] The difference from Example 1 is that 50 mL of 6.3 g / L polyvinyl pyrrolidone aqueous solution is omitted, and the rest is the same as Example 1.
[0083] Figure 1 1% Pd / V-CN ( Figure 1 SEM images of (a) in the figure and 1% Pd / CN prepared in comparative example 1 ((b) in the figure). The 1% Pd / V-CN sample has a loose two-dimensional nano-thin layer structure. This structure is caused by the molecular structure of the carbon-nitrogen polymer material changing during the thermal stripping process, overcoming the interaction force between the layers, causing the layers to peel off and become thinner, forming a two-dimensional nanosheet with clear edges. The 1% Pd / CN sample presents a stacked block morphology, with the layers tightly bonded, lacking significant stripping characteristics, and showing a denser structure.
[0084] Figure 2 A spherical aberration-corrected transmission electron micrograph of 1% Pd / V-CN prepared in Example 1 of the present invention is shown. The figure shows that palladium clusters of about 2 nanometers in size are distributed at the edges of carbon-nitrogen polymer nanosheets, showing a phenomenon of preferential growth. This is because the unsaturated active sites present at the edges, such as carbon vacancies and cyano sites, provide ideal conditions for the attachment and growth of palladium clusters. The observed palladium lattice spacing is 0.225 nanometers, corresponding to the (111) crystal plane of the face-centered cubic (FCC) crystal phase, which is more likely to be preferentially grown on palladium atoms at the nanoscale due to its lower surface energy. This uniform distribution and preferential growth characteristics not only improve the utilization rate of palladium and increase the number of active sites, but also significantly improve the catalytic efficiency and effectively avoid catalyst failure caused by palladium cluster agglomeration.
[0085] Figure 3This is a spherical aberration corrected transmission electron micrograph of 1% Pd / CN prepared in comparative example 1 of the present invention. This image shows that palladium nanoparticles have obvious agglomeration on the bulk carbonitride polymer block, and the particle size ranges from less than 2 nanometers to about 8 nanometers. Agglomeration leads to a reduction in active surface area, thereby reducing catalytic efficiency.
[0086] Figure 4 The nitrogen adsorption-desorption curves and pore size distribution diagrams of 1% Pd / V-CN prepared in Example 1 of the present invention and 1% Pd / CN prepared in Comparative Example 1 are shown. The adsorption curve of 1% Pd / V-CN has typical IV type isotherm characteristics and is accompanied by obvious hysteresis loops, indicating the presence of its mesoporous structure. This mesoporous structure provides a larger reaction channel, which helps to improve the mass transfer performance and reaction efficiency of the catalyst.
[0087] Table 1 shows the analysis results of the specific surface area, pore size and pore volume of 1% Pd / V-CN prepared in Example 1 of the present invention and 1% Pd / CN prepared in Comparative Example 1. The specific surface area of 1% Pd / V-CN is 71.2 m 2 / g, much higher than 4.9m / g of 1% Pd / CN 2 / g, indicating that 1% Pd / V-CN has larger surface active sites. The pore volume of 1% Pd / V-CN also increases significantly, reaching 0.42 cm 3 / g, and the pore size is 23.6nm, which further confirms that it has an open mesoporous structure. The larger pore volume provides a larger reaction channel and promotes the effective transport of reactants.
[0088] Table 1
[0089]
[0090] Figure 5 The X-ray powder diffraction patterns of the catalysts prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention are shown. Compared with CN, the decrease in the XRD diffraction peak intensity of V-CN is due to the fact that the thermal stripping process destroys the layered structure of the carbon-nitrogen polymer material, resulting in more defects and unsaturated sites, causing structural disorder, resulting in a decrease in the order of the crystal. The diffraction peaks of the Pd / V-CN catalyst at 12.8° and 27.3° belong to the crystal plane diffraction peaks of the carbon-nitrogen polymer material substrate, indicating that its crystal structure is still retained after stripping. The Pd (111) characteristic diffraction peak was observed at 39.7°, indicating that palladium was successfully loaded on the carbon-nitrogen polymer substrate, and palladium exists in a face-centered cubic (FCC) crystal form, which is consistent with the JCPDS card number 05-0681.
[0091] Figure 6The infrared spectra of the catalysts prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention are shown. It can be seen from the infrared spectrum analysis that the skeleton structure of Pd / V-CN and V-CN does not change significantly after thermal stripping and palladium loading, especially the cyanide vibration absorption peak clearly observed at 2170cm-1, indicating that these two materials contain cyanide. However, no characteristic peak of cyanide was detected in CN and Pd / CN samples, indicating that they do not contain cyanide. At the same time, the fingerprint vibration peak of the oxazine ring at 810cm-1 further confirms that these materials contain a carbon-nitrogen polymer structure composed of oxazine rings.
[0092] Figure 7 The total ion current chromatogram of the 1% Pd / V-CN dipentene dehydrogenation product prepared in Example 1 of the present invention is shown. Figure 7 (a) in the figure, the main product is p-cymene, the peak appears at around 12.267 minutes, and the peak intensity is very significant, indicating that the catalyst is highly selective for the formation of p-cymene. When 1% Pd / CN catalyst is used (see Figure 7 In (b)), the peak of p-cymene appears at 11.963 minutes. Although it is still the main product, its peak area and peak intensity are relatively low, indicating that the selectivity and activity of this catalyst are not as good as those of Pd / V-CN.
[0093] Table 2 shows the integrated peak list of the GC / MS chromatogram report of the dipentene dehydrogenation product of 1% Pd / V-CN prepared in Example 1 of the present invention. According to the data, p-cymene is the main product, and the relative content of p-cymene in the product is 99.5%, but there are also small amounts of p-menane (0.2%) and dipentene (0.3%). In the dipentene dehydrogenation reaction catalyzed by 1% Pd / V-CN, the conversion rate is as high as nearly 100%, and the selectivity is nearly 100%, showing that Pd / V-CN has an excellent catalytic effect in the dipentene dehydrogenation reaction.
[0094] Table 2
[0095]
[0096] Table 3 shows the integrated peak list of the GC / MS chromatogram report of the dipentene dehydrogenation product of 1% Pd / CN prepared in Comparative Example 1 of the present invention. Although p-cymene is the main product, there are still many by-products in the reaction. The residual dipentene reactant accounts for 26.8%, as well as disproportionation reaction intermediates such as 4-methyl-1-isopropylcyclohexene (5.8%) and 3-methyl-6-(1-methylethyl)cyclohexene (3.8%). This shows that the conversion rate of dipentene in the dipentene dehydrogenation reaction of 1% Pd / CN catalyst is 73.3%, the selectivity of p-cymene is 83.9%, and the relative content of p-cymene in the product is 61.5%, showing poor catalytic performance.
[0097] Table 3
[0098]
[0099] pass Figure 7 From the analysis of Table 2 and Table 3, it can be seen that the selectivity and catalytic performance of the 1% Pd / V-CN catalyst in the dehydrogenation reaction of dipentene are significantly better than those of the 1% Pd / CN catalyst, especially in the formation of the target product cymene, which shows higher selectivity and less by-product formation.
[0100] Table 4 shows the results of the conversion of dipentene and the selectivity of p-cymene in Examples 1-7 and Comparative Examples 1-8 of the present invention. The Pd / V-CN catalyst used in the examples is excellent in terms of conversion, selectivity and the relative content of p-cymene in the product, especially when the palladium loading is 1%, 1% Pd / V-CN (Example 1), its conversion is as high as nearly 100%, the selectivity is nearly 100%, and the relative content of p-cymene reaches 99.5%, which is the most outstanding performance. When the palladium loading is increased to 4%, the conversion rate is only slightly improved, indicating that the catalyst has achieved the best effect under low palladium loading, and further increasing the palladium loading has limited improvement on the catalytic effect. In contrast, the performance of comparative catalysts such as 1% Pd / CN (Comparative Example 1) and 10% palladium carbon (Comparative Example 4), 3% Pd / PHI (Comparative Example 7) is relatively inferior, and the relative content of p-cymene is lower than that of Pd / V-CN catalyst. In addition, other comparative catalysts such as Raney nickel and HZSM-5 molecular sieves performed worse, especially in the relative content of para-cymene, which was only 27.5% and 16.5%, respectively. Overall, the Pd / V-CN catalyst outperformed other catalysts in all indicators, especially 1% Pd / V-CN, which showed the best catalytic effect in the dehydrogenation reaction of dipentene. At the same time, when the reactant industrial dipentene was replaced with pinene, γ-terpinene or limonene, the Pd / V-CN catalyst still maintained good catalytic activity, which shows that the Pd / V-CN catalyst exhibits broad-spectrum catalytic activity and high selectivity, making it have great application potential in a variety of olefin dehydrogenation reactions and showing feasibility in industrial-scale production.
[0101] Table 4
[0102]
[0103]
[0104] Table 5 shows the results of the cyclic experiment of 1% Pd / V-CN prepared in Example 1 of the present invention in the dehydrogenation reaction of dipentene. After catalyzing the dehydrogenation reaction of dipentene, the 1% Pd / V-CN catalyst was centrifugally washed (centrifugal speed 10000 rpm, each centrifugation time was 3 min) 3 times, dried (dried at 60°C for 12 hours, naturally cooled to room temperature), ground with an agate mortar to obtain a solid powder with a particle size of less than 100 microns, and the 1% Pd / V-CN catalyst of the first cycle was recovered (the mass recovery rate of the catalyst was maintained at more than 95%), and used as the catalyst for the second cycle. According to this step, 15 rounds of cyclic reactions were carried out in sequence, and the cyclic stability of the catalyst was analyzed. The results showed that after 15 cyclic experiments, the conversion rate of dipentene (industrial dipentene) of the 1% Pd / V-CN catalyst was still maintained at more than 98%, the selectivity of p-cymene was also maintained at more than 97%, and the relative content of p-cymene in the product was more than 96%. This shows that the 1% Pd / V-CN catalyst has good cyclic stability. Compared with the commercial 10% Pd-on-carbon catalyst (Table 7), the activity decay of 1% Pd / V-CN is smaller and its service life is significantly extended, further demonstrating its excellent long-term catalytic performance.
[0105] Table 5
[0106]
[0107]
[0108] Table 6 shows the results of the cyclic experiment of 1% Pd / CN prepared in Comparative Example 1 of the present invention in the dehydrogenation reaction of dipentene. The activity of the 1% Pd / CN catalyst in the dehydrogenation reaction of dipentene is relatively low but stable: the conversion rate gradually decreases from 73.3% to 69.0%, the selectivity of p-cymene is maintained between 83.9% and 80.7%, and the relative content of p-cymene in the product also decreases from 61.5% to 56.0%. Although the catalyst has good stability in multiple cyclic experiments, its activity level is low, which may limit its application potential in the demand for high-efficiency catalysis.
[0109] Table 6
[0110]
[0111]
[0112] Table 7 is the cycle test result of commercial 10% palladium carbon catalyst in dipentene dehydrogenation reaction. The activity, selectivity and product purity of commercial 10% palladium carbon catalyst in dipentene dehydrogenation reaction all significantly decrease with the increase of cycle number, indicating that the cycle stability of the catalyst is poor. Therefore, from the data of Table 5-Table 7, it can be seen that compared with 1% Pd / CN and commercial 10% palladium carbon catalyst, 1% Pd / V-CN catalyst has higher conversion rate, selectivity and better cycle stability, showing more excellent catalytic performance and stability. Compared with traditional 10% palladium carbon catalyst, the palladium loading used by 1% Pd / V-CN catalyst of the present invention is reduced by 90%, which significantly reduces the use cost of palladium, and can still maintain high conversion rate and high selectivity in catalytic performance.
[0113] Table 7
[0114]
Claims
1. A method for preparing palladium clusters with precise positioning at the edge of a nanosheet, characterized in that: A nitrogen-containing precursor is subjected to a first calcination to obtain a carbon-nitrogen polymer solid powder, which is then subjected to a second calcination. A cyano-modified carbon-nitrogen polymer nanosheet with highly active edge sites is formed through a thermal stripping process. Palladium is precisely positioned through the strong coordination between the cyano group and the edge active sites, and the palladium clusters are further dispersed better at the edge of the nanosheet by adding a stabilizer in combination with a chemical reduction method, thereby obtaining a palladium cluster with precise positioning at the edge of the nanosheet; the loading amount of palladium relative to the cyano-modified carbon-nitrogen polymer nanosheet carrier is 0.5-1.5wt%; the stabilizer is at least one of polyvinyl pyrrolidone, polyethylene glycol, polyethyleneimine, polyvinyl alcohol or sodium carboxymethyl cellulose.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the cyano-modified carbon-nitrogen polymer nanosheets to the stabilizer is 1:(0.5-10), and the concentration of the stabilizer is 1-10 g / L.
3. The preparation method according to claim 1 or 2, characterized in that: The stabilizer is polyvinyl pyrrolidone.
4. The preparation method according to claim 1 or 2, characterized in that: Metal palladium is loaded on cyano-modified carbon nitrogen polymer nanosheets by a chemical reduction method. The specific steps include: uniformly mixing cyano-modified carbon nitrogen polymer nanosheet catalyst powder, water and stabilizer, then adding palladium chloride-hydrochloric acid solution, and heating in an oil bath for reaction; then adjusting the pH to alkaline, adding sodium borohydride solution for reduction, and then centrifuging, washing with water, washing with ethanol, vacuum drying and grinding in sequence to obtain a palladium cluster catalyst with precise positioning on the edge of the cyano-modified carbon nitrogen polymer nanosheet.
5. The preparation method according to claim 4, characterized in that: The mass volume ratio of the cyano-modified carbon-nitrogen polymer nanosheet to the palladium chloride-hydrochloric acid solution is 1:(3-10); the mass volume ratio of the cyano-modified carbon-nitrogen polymer nanosheet to sodium borohydride is 1:(0.01-0.1).
6. The preparation method according to claim 1 or 2, characterized in that: In the first calcination process, the nitrogen-containing precursor is calcined in a muffle furnace or a tube furnace with a heating rate of 2-4°C / min and a holding temperature of 470-600°C, and is maintained at this temperature for 3-5 hours in an atmosphere of atmospheric pressure air or inert gas, and then naturally cooled to room temperature and ground into a carbon-nitrogen polymer powder.
7. The preparation method according to claim 1 or 2, characterized in that: The nitrogen-containing precursor includes at least one of melamine, cyanamide, dicyandiamide, urea, cyanuric acid, thiourea, ammonium thiocyanate, guanidine thiocyanate, guanidine hydrochloride, semicarbazide, aminoguanidine, 2,4,6-triamino-1,3,5-triazine or 5-aminotetrazole.
8. The preparation method according to claim 1 or 2, characterized in that: The carbon-nitrogen polymer solid powder obtained by the first calcination is placed in a muffle furnace or a tubular furnace for a second calcination, with a heating rate of 0.5-1.5°C / min, heated to 200-300°C, and maintained at this temperature for 1-3 hours. The atmosphere in the muffle furnace is atmospheric pressure air or inert gas, and then naturally cooled to room temperature and ground into cyano-modified carbon-nitrogen polymer nanosheet solid powder.
9. An application of palladium clusters for precise positioning of nanosheet edges obtained by the preparation method according to any one of claims 1 to 8, characterized in that: As a catalyst, it is used for the catalytic dehydrogenation of dipentene to prepare p-cymene; The method for preparing p-cymene by catalytic dehydrogenation of dipentene comprises: stirring and mixing a catalyst and dipentene, placing the mixture in a reactor for reaction, filtering and separating the catalyst after the reaction, and analyzing the obtained liquid product by gas chromatography-mass spectrometry; centrifuging the catalyst, washing the precipitate, drying and grinding the precipitate, and then reusing the precipitate.
10. The use according to claim 9, characterized in that: The mass ratio of the palladium cluster catalyst to dipentene is precisely positioned at (0.005-0.01):1, the reaction temperature is 150-210°C, the reaction time is 0.5-2 hours, the reaction pressure is 0.05-3MPa, the reaction atmosphere is argon or nitrogen, and the stirring speed is 100-1000rpm / min.